Nephrogenic systemic fibrosis: Review of 408 biopsy-confirmed cases - Zhitong Zou; Lin Ma (Wolters Kluwer Medknow Publications, 2011)
Nephrogenic systemic fibrosis (NSF) has now been virtually eliminated by the discovery of its association with gadolinium-based contrast agents (GBCAs) and the consequent reduced use of GBCA-enhanced magnetic resonance imaging (MRI) in severe renal failure patients. This review of 408 biopsy-confirmed cases shows how to minimize NSF risk when performing GBCA-enhanced MRI or magnetic resonance angiography. The absence of any NSF cases in patients less than 8 years old or greater than 87 years old suggests that infants and elderly patients are already protected. Limiting GBCA dose to a maximum of 0.1 mMol/kg, dialyzing dialysis patients quickly following GBCA administration, delaying administration of GBCA in acute renal failure until after renal function returns or dialysis is initiated, and avoiding nonionic linear GBCA in renal failure patients, especially when there are pro-inflammatory conditions, appear to have reduced NSF risk to the point where safe GBCA-enhanced MRI is possible in most patients.